1975
DOI: 10.2307/3428421
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals in Occupationally and Nonoccupationally Exposed Individuals

Abstract: An epidemiological survey was conducted in Houston, Texas on five trace metals in policemen, parking garage attendants, women living near freeways and three control groups of subjects. The controls were mnatched with the exposed groups for covariate information such as age, sex, smoking habits, ethnic background, socioeconomic status, hair color, and education. Each subject was sampled four times for blood, urine, hair, and feces, and these samples were analyzed for lead, cadmium, zinc, manganese, and copper. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The average daily fecal cadmium varied between 41 and 79 ,g with an overall average of 56 ,g. The laboratory in Gifu participated in the interlaboratory crosscheck study of cadmium analysis (Kjellstrom and Linnman, to be published) and their results agreed well with the other laboratories. One additional study (EPAISWRI) had been carried out in the U.S. (29,30) on 216 volunteers from Houston in the age range 20-49. Overnight specimens of feces were collected, and 24-hr fecal amounts were not measured. The analytical method was different from the one used for the study in Dallas described above.…”
Section: Fecal Cadmium Contentmentioning
confidence: 99%
“…The average daily fecal cadmium varied between 41 and 79 ,g with an overall average of 56 ,g. The laboratory in Gifu participated in the interlaboratory crosscheck study of cadmium analysis (Kjellstrom and Linnman, to be published) and their results agreed well with the other laboratories. One additional study (EPAISWRI) had been carried out in the U.S. (29,30) on 216 volunteers from Houston in the age range 20-49. Overnight specimens of feces were collected, and 24-hr fecal amounts were not measured. The analytical method was different from the one used for the study in Dallas described above.…”
Section: Fecal Cadmium Contentmentioning
confidence: 99%
“…The catalysts used small quantities of platinum and palladium, and there have been some indications of emissions of particles of these metals. Health effects of exposure to platinum and palladium reviewed in a previous study (1) indicated that soluble forms of platinum can create allergic responses in sensitive individuals. However, little information is available concerning long-term chronic exposure of humans to low levels of platinum or palladium, in particular for groups that may be at greater risk such as the young or aged and for individuals with some type of medical impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Study design provided for equal numbers of volunteer participants in each of three age groupings: age group I, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] years; age group II, 17-34 years; and age group III, 35 and over. Approximately 150 individuals were initially selected for study in each of the two areas, 50 in each age group.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (1975) compared the urinary lead concentrations of several groups of people in Houston, Texas. For non-exposed control s, mean urinary lead concentrations ranged from 19.0-27.8 tLg/l; the same groups also had lead in the hair at levels ranging from 6.0-29.7 mg/kg and in the faeces, from 2.2-2.7 mg/kg.…”
Section: Iarc Monographs Volume 23mentioning
confidence: 99%